The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15517/rbt.v68is2.44332
|View full text |Cite
|
Sign up to set email alerts
|

Variación estacional y características fisicoquímicas e hidrológicas que influyen en los macroinvertebrados acuáticos, en un río tropical

Abstract: Introducción: La distribución de los macroinvertebrados acuáticos en los ríos puede estar determinada por el tipo del sustrato, la forma del canal del río, el régimen hidrológico y las interacciones con factores bióticos y abióticos. En Costa Rica se desconoce en gran parte de los ríos, las variaciones en la distribución de los macroinvertebrados acuáticos producto de las transiciones y consecuentes variaciones en características fisicoquímicas e hidrológicas. Objetivos: 1) Estudiar el cambio del ensamblaje de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…So that high areas of a basin may have greater diversity because the variations of flows given by the slopes allows greater heterogeneity in the landscape than in the low sections where the slope decreases as well as flow (Mesa, 2010). Likewise, when the flow increases in the rainy season, the communities are modified (Quesada-Alvarado et al, 2020). Therefore, it is important to consider the seasonality of the samples, being also throughout the year that differences have been seen in the macroinvertebrate assemblages as the flows and chemical composition of the rivers is modified, for example, by the leachate of the soil in rainy season (Leal-Bastidas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…So that high areas of a basin may have greater diversity because the variations of flows given by the slopes allows greater heterogeneity in the landscape than in the low sections where the slope decreases as well as flow (Mesa, 2010). Likewise, when the flow increases in the rainy season, the communities are modified (Quesada-Alvarado et al, 2020). Therefore, it is important to consider the seasonality of the samples, being also throughout the year that differences have been seen in the macroinvertebrate assemblages as the flows and chemical composition of the rivers is modified, for example, by the leachate of the soil in rainy season (Leal-Bastidas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…So that high areas of a basin may have greater diversity because the variations of flows given by the slopes allows greater heterogeneity in the landscape than in the low sections where the slope decreases as well as flow (Mesa, 2010). Likewise, when the flow increases in the rainy season, the communities are modified (Quesada-Alvarado et al, 2020). Therefore, it is important to consider the seasonality of the samples, being also throughout the year that differences have been seen in the macroinvertebrate assemblages as the flows and chemical composition of the rivers is modified, for example, by the leachate of the soil in rainy season (Leal-Bastidas et al, 2021).…”
mentioning
confidence: 99%
“…Several studies on the ecology of aquatic insects in Latin America have been reported, with emphasis on the relationship with abiotic factors (Ramírez & Gutierrez-Fonseca, 2014a). For example, recently, Kohlmann et al (2021) include in their study a analyzes of the relationships between functional feeding groups of aquatic macroinvertebrates with physicochemical such as NO 3− K + , biochemical oxigen demand (BDO), oxygen saturation, and pH; Díaz-Rojas et al (2020) relates depth, flow velocity, channel width and roughness of the substrate with macroinvertebrate assemblages composition and functional traits; Quesada-Alvarado et al (2020) describe the relationship between the aquatic macroinvertebrate assemblages with physicochemical and habitat variables, such as NO 3− , substrate and flow; and, Mosquera-Restrepo & Peña-Salamanca (2019) explain the relationships between aquatic macroinvertebrates assemblages with dissolved oxygen, BOD, total dissolved solids, and turbidity.…”
mentioning
confidence: 99%